До історії вивчення аттичної чорнолакової кераміки з Північного Причорномор'я - Чечуліна, І.О. (Археологія, 2015)
Огляд історії вивчення аттичної чорнолакової кераміки, що походить з розкопок античних пам’яток Північного Причорномор’я, дав змогу виділити три основні етапи в дослідженні цього різновиду довізного посуду. Охарактеризовано нинішній стан його вивчення у різних центрах регіону. В статье проанализированы работы отечественных исследователей, посвященные аттической чернолаковой ке рамике из античных центров северного Причерноморья. исследование аттической чернолаковой керамики раз делено на три этапа: рубеж XiX—XX вв. — до начала 1940х гг. — начало изучения посуды этого вида, описание материалов; 1950—70е гг. — появление работ с детальной датировкой, комплексное исследование керамики; с 1970х гг. — составление типологий и классификаций. к первому этапу относятся отчеты, публикации материалов из раскопок, где порой авторы уделяли внимание и чернолаковой керамике, работы в основном носят описательный характер, редко встречаются фотографии и рисунки. с 1920х гг. публикуются массовые находки чернолаковой посуды не только с некрополей, но и из рас копок поселений. На втором этапе появляются первые обобщающие труды, посвященные расписной керамике, где значительное место занимает чернолаковая посуда. Больше внимания исследователи уделяют хронологии, изменению морфологии форм, качеству лака. значительную роль на этом этапе играют труды, характеризующие керамические комплексы поселений. современный этап исследования аттической чернолаковой керамики знаменуют фундаментальные разработ ки массовых материалов Афинской агоры в середине 1970х гг. Все больше внимания уделяется аттической чер нолаковой керамике, как основному датирующему критерию. рассматриваются коллекции материалов из посе лений, составляются каталоги. работы, посвященные аттической чернолаковой керамике из городов северного Причерноморья разделены на: работы по исследованию городищ, поселений и некрополей. среди исследований некрополей много таких, где среди всего инвентаря вовсе не выделяют чернолаковую керамику. Особое внима ние привлекают работы, где приводится типология этой посуды определенных видов. The main works by homeland researchers on Attic blackglazed pottery from the Ancient Greek centres on the north coast of the Black sea are analyzed in the article. the study of Attic blackglazed ware is divided into three stages: from the edge of the 19th and the 20th centuries to the early 1940s, the beginning of the research of this type of pottery and the description of archaeological materials; the 1950s—1970s, the appearance of works with detailed dating and apprehensive pottery research; since the 1970s, the development of typologies and classifications. the first stage includes reports and publications of materials from the excavations, in which the authors sometimes paid attention to the blackglazed pottery, and which were descriptive with occasional photographs and drawings. since the 1920s, there were published bulk finds of blackglazed pottery not only from necropolei, but also from the excavations at settlements. At the second stage, the first generalizing works appeared in which blackglazed pottery played a significant role. the researchers paid more attention to the chronology, the changes in forms morphology, and glaze quality. At this stage, works characterizing ceramic assemblages of settlements become playing a significant role. the current stage of blackglazed pottery research is marked by fundamental developments of archaeological bulk material from the Athenian agora made in the mid 1970s. More attention is devoted to blackglazed pottery as the main dating criterion. Collections of materials from settlements are discussed and the catalogues are made. the works devoted to Attic blackglazed pottery from the ancient cities of the north coast of the Black sea are divided into the following groups: research at the hillforts, settlements, and necropoleis. Among the necropoleis studies, there are many in which the black glazed pottery is not separated among other inventory at all. special attention is drawn to the works that provide the typology of certain types of this ware.